Design and Implementation of a Multivariable Decoupling Control System for HPAL Autoclave with Web-Based SCADA Interface - Afandy Moh; Yulianti Malik; Abdul Haris Mubarak; Muhammad Ikbal Rianto (Journal of Renewable Energy and Smart Device, 2026)
This study presents the design and experimental evaluation of a laboratory-scale High-Pressure Acid Leaching (HPAL) autoclave integrating a Siemens S7-1200 programmable logic controller (PLC), Modbus RTU industrial communication, an Internet of Things (IoT) gateway, and a cloud-based Web-SCADA platform for real-time monitoring and process supervision. The platform was developed to provide a safe laboratory-scale environment for hydrometallurgical process experimentation and industrial automation education under a lower-severity operating envelope than industrial HPAL systems. Experimental validation was conducted using limonite laterite nickel ore with nominal sulfuric acid concentrations of 4 wt.% and 5 wt.% in single experimental runs at a reactor temperature setpoint of 150°C. The implemented closed-loop ON–OFF controller with hysteresis maintained the reactor temperature near the setpoint after a heating period of approximately 1.48 h, while the stirring system operated within 188–192 rpm and the reactor pressure remained stable at approximately 3.2–3.4 bar throughout the holding period. Continuous data acquisition and visualization through the Web-SCADA platform were achieved without communication interruption between the PLC, IoT gateway, and cloud server during the experiments. The leaching process produced liquid filtrate and solid residue, with measured solution volume reductions of 15% for the nominal 4 wt.% sulfuric acid experiment and 12% for the nominal 5 wt.% sulfuric acid experiment. These observations represent process validation only, as comprehensive metallurgical evaluation, including nickel recovery and extraction efficiency, was beyond the scope of this study. The results demonstrate the feasibility of integrating industrial automation, IoT communication, and cloud-based monitoring into a laboratory-scale HPAL platform for process control, data acquisition, and engineering education.